PENGARUH MEDIA WORDWALL TERHADAP KEMAMPUAN BERPIKIR KRITIS PESERTA DIDIK KELAS V UPTD SDN MANO`AN 3 BANGKALAN - Agustina Khomsya Laili Briliant Putri; Satianingsih, Rarasaning (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Critical thinking is a 21st-century skill that must be developed since elementary school. However, the development of this ability is still not optimal due to the use of learning media that is less varied and conventional. This study aims to determine the effect of wordwall media on the critical thinking ability of fifth-grade students at the UPTD SDN Mano'an 3 Bangkalan. The method used is quantitative with a Quasi Eksperimental Posttest Only Non-Equivalent Group Design. The study involved 30 fifth-grade students, selected by total sampling, with two groups of students as research samples. The experimental group used wordwall learning media, while the control group used conventional learning. Data collection was carried out through a critical thinking ability test covering 3 indicators of critical thinking, namely focusing on questions, analyzing arguments, and determining an action. The research instrument used essay-based posttest questions. Data were analyzed using statistical test using IBM spss 21. The results of the study showed that the average critical thinking ability of students in the experimental group. Students who learned using wordwalls were better able to understand the core of the problem, analyze informatiom or provide logical reasons, and determine answers based on appropriate considerations. Wordwall media provides opportunities for students to learn actively, try again when making mistakes, and receive direct feedback. In conclusion, the use of wordwall media has a positive effect on the critical thinking skills of fifth-grade students at the UPTD SDN Mano'an 3 Bangkalan.